16 Days Campaign, Albania, Bulgaria, Croatia, Georgia, Moldova, Montenegro, Serbia, Slovakia, Ukraine
Eleven public service announcement on the tape. In order: 1. Slovakia (in Slovakian) 2. Croatia (in Croatian) 3. Georgia (in Georgian) 4. Bulgaria (in Bulgarian) 5. Moldova (in Romanian) 6. Serbia (in Serbian) 7. Serbia (in Serbian) 8. Ukraine (in Ukrainian) 9. Montenegro (in Serbian Ijekavian dialect), 10. Albania (in Albanian) 11. Ukraine (in Ukrainian); Country: Albania, Bulgaria, Croatia, Georgia, Moldova, Slovakia, Ukraine, Yugoslavia